JURIDICAL REVIEW FULFILLMENT OF JUSTICE PRINCIPLES IN ELIMINATION OF TAX SANCTIONS IN LAW NUMBER 11 OF 2016 - Siska Johan (Faculty of Law, Universitas Riau, 2019)
The objectives of this research are to know: (1) the fulfillment of the principle of justice for the elimination of tax sanctions in Law number 11 of 2016 concerning tax amnesty; (2) forgiveness which eliminates tax sanctions from a justice perspective.This research is a type of normative research, namely a process to find the rule of law, legal principles and legal doctrines to answer legal problems.The results of this study indicate that the principle of fairness towards the elimination of tax in Law number 11 of 2016 concerning tax amnesty has not been fulfilled because one of the principle of fairness has not fulfilled. The principle of justice according to Adam Smith: 1) Principle of equality and justice (equity). The principle of equality means that people who are in the same condition must be subject to the same tax, 2) Principle of certainty. This principle provides a guarantee of legal protection against taxpayers is the purpose of each law. 3) Compliance with Tax Payments after the enactment of Law number 11 of 2016 concerning tax amnesty.